A marine fungus‐derived nitrobenzoyl sesquiterpenoid suppresses receptor activator of NF‐κB ligand‐induced osteoclastogenesis and inflammatory bone destruction. (11th August 2020) - Tan, Yanhui; Deng, Wende; Zhang, Yueyang; Ke, Minhong; Zou, Binhua; Luo, Xiaowei; Su, Jianbin; Wang, Yiyuan; Xu, Jialan; Nandakumar, Kutty Selva; Liu, Yonghong; Zhou, Xuefeng; et al.
Abstract : Background and Purpose: Osteoclasts are unique cells to absorb bone. Targeting osteoclast differentiation is a therapeutic strategy for osteolytic diseases. Natural marine products have already become important sources of new drugs. The naturally occurring nitrobenzoyl sesquiterpenoids first identified from marine fungi in 1998 are bioactive compounds with a special structure, but their pharmacological functions are largely unknown. Here, we investigated six marine fungus‐derived nitrobenzoyl sesquiterpenoids on osteoclastogenesis and elucidated the mechanisms. Experimental Approach: Compounds were first tested by RANKL‐induced NF‐κB luciferase activity and osteoclastic TRAP assay, followed by molecular docking to characterize the structure–activity relationship. The effects and mechanisms of the most potent nitrobenzoyl sesquiterpenoid on RANKL‐induced osteoclastogenesis and bone resorption were further evaluated in vitro. Micro‐CT and histology analysis were used to assess the prevention of bone destruction by nitrobenzoyl sesquiterpenoids in vivo. Key Results: Nitrobenzoyl sesquiterpenoid 4, with a nitrobenzoyl moiety at C‐14 and a hydroxyl group at C‐9, was the most active compound on NF‐κB activity and osteoclastogenesis. Consequently, nitrobenzoyl sesquiterpenoid 4 exhibited suppression of RANKL‐induced osteoclastogenesis and bone resorption from 0.5 μM. It blocked RANKL‐induced IκBa phosphorylation, NF‐κB p65 and RelB nuclear translocation, NFATc1 activation, reduced DC‐STAMP but not c‐Fos expression during osteoclastogenesis in vitro. Nitrobenzoyl sesquiterpenoid 4 also ameliorated LPS‐induced osteolysis in vivo. Conclusion and Implications: These results highlighted nitrobenzoyl sesquiterpenoid 4 as a novel inhibitor of osteoclast differentiation. This marine‐derived sesquiterpenoid is a promising lead compound for the treatment of osteolytic diseases. Abstract :